Pembentukan Karakter Pemimpin Kristen Yang Unggul Di Era Milenial - Thobias, Apriati Woi Sawanen (Sekolah Tinggi Teologi Kharisma, 2020)
The development of increasingly advanced technology has influenced the lives of believers, one of which is gadgets. Gadgets are a daily necessity and even a basic necessity. This development is very good. However, not all of these developments must be followed. Even Christian youths are involved in the alcohol trend. This is not a good situation. Christian leaders need to see and anticipate this so that the congregation does not carry on with the flow of developments that will distract people from the life that should be an example for their surroundings. The method used by the author is a qualitative method. Qualitative Method because of the problem regarding the decline of Christian leadership in the Millennial Era. In this era, Christian leaders who are superior in character are needed. Not a few of Christian leaders do not care about their character. This requires the willingness of Christian leaders who want to build their character so that they become superior and capable Christian leaders. Because without good character, leaders are unable to lead. Character is the main thing that is prepared by Christian leaders to become leaders. Perkembangan teknologi yang makin maju ini telah mempengaruhi kehidupan orang percaya, salah satunya adalah gadget. Gadget menjadi kebutuhan sehari-hari bahkan menjadi kebutuhan pokok. Perkembangan ini sangat baik. Namun tidak semua perkembangan itu harus diikuti. Bahkan ada anak-anak muda Kristen pun terlibat dalam tren miras. Ini merupakan keadaan yang tidak baik. Pemimpin Kristen perlu melihat dan mengantisipasi hal ini agar jemaat tidak berbawa arus perkembangan yang akan menjauhkan mereska dari kehidupan yang harusnya menjadi teladan bagi sekitarnya. Metode yang digunakan oleh penulis adalah metode kualitatif. Metode Kualitatif karena persoalannya mengenai kemerosotan kepemimpinan Kristen di Era Millenial. Di Era ini sangat diperlukan pemimpin Kristen yang unggul dalam karakternya. Tidak sedikit dari pemimpin Kristen tidak peduli akan karakternya. Untuk itu diperlukan kesediaan pemimpin Kristen yang mau dibangun karakternya agar menjadi pemimpin Kristen yang unggul dan mampu memimpin. Sebab tanpa karakter yang baik, pemimpin tidak mampu memimpin. Karakterlah yang utama dipersiapkan pemimpin Kristen untuk menjadi pemimpin.